Feasibility Exploration of Electrodermal Response to Food in Children with ASD Compared to Typically Developing Children - Michelle A. Suarez (Scholarworks @ WMU, 2018)
Background: Children with Autism Spectrum Disorder (ASD) frequently have food selectivity that causes additional health and quality of life stressors for the child and the family. The causes of food selectivity are currently unknown but may be linked, at least in part, to sensory processing problems. Method: The purpose of this study was to test the feasibility of using electrodermal activity (EDA) measurement in response to food to gain insight into the physiological processes associated with eating for children with ASD compared to typically developing children. In addition, differences in food acceptance and the relationship between food acceptance and sensory over-responsivity were explored. Results: Children with ASD had significantly different EDA during food presentation compared to typically developing controls. In addition, children with ASD accepted significantly fewer foods as part of their regular diet, and the number of foods accepts was significantly related to a measure of SOR. Discussion: This information has the potential to inform research and treatment for food selectivity